2016
DOI: 10.1136/bmj.i2375
|View full text |Cite
|
Sign up to set email alerts
|

Late mortality after sepsis: propensity matched cohort study

Abstract: Objectives To determine whether late mortality after sepsis is driven predominantly by pre-existing comorbid disease or is the result of sepsis itself.Deign Observational cohort study.Setting US Health and Retirement Study.Participants 960 patients aged ≥65 (1998-2010) with fee-for-service Medicare coverage who were admitted to hospital with sepsis. Patients were matched to 777 adults not currently in hospital, 788 patients admitted with non-sepsis infection, and 504 patients admitted with acute sterile inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
225
2
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 265 publications
(244 citation statements)
references
References 42 publications
8
225
2
9
Order By: Relevance
“…However, even in well-controlled studies, it is difficult to identify among these factors those related to the sepsis-attributable mortality. A recent controlled study showed that late excess mortality was higher in patients with 3 or more organ dysfunctions, even after adjusting for acute mortality differences [141]. Another recent study observed these [141] effects were significantly higher in male patients, younger patients, those with higher Charlson Comorbidity Index scores, those with higher numbers of organ failure, those admitted to intensive care units, those with shock, and those who required mechanical ventilatory support [142].…”
Section: What Are the Predictors Of Sepsis Long-term Morbidity And Momentioning
confidence: 99%
See 1 more Smart Citation
“…However, even in well-controlled studies, it is difficult to identify among these factors those related to the sepsis-attributable mortality. A recent controlled study showed that late excess mortality was higher in patients with 3 or more organ dysfunctions, even after adjusting for acute mortality differences [141]. Another recent study observed these [141] effects were significantly higher in male patients, younger patients, those with higher Charlson Comorbidity Index scores, those with higher numbers of organ failure, those admitted to intensive care units, those with shock, and those who required mechanical ventilatory support [142].…”
Section: What Are the Predictors Of Sepsis Long-term Morbidity And Momentioning
confidence: 99%
“…The review's conclusion was subsequently challenged by two well-designed studies. One study showed that mortality was increased, compared with matched non-hospitalized controls, non-septic infected hospitalized patients and patients admitted with sterile inflammatory conditions [141]. Another study demonstrated that septic patients had higher mortality than matched controls from the general population and subjects who were hospitalized for a non-septic cause [142].…”
Section: Post-icumentioning
confidence: 99%
“…A maioria das mortes ocorreu nos primeiros seis meses, mas o risco permaneceu elevado aos dois anos. Após a alta do hospital, a sepse comporta um maior risco de morte (até 20%), bem como um risco aumentado de sepse adicional e internações hospitalares recorrentes (até 10% são readmitidos) (15)(16)(31)(32) . …”
Section: Discussionunclassified
“…What these studies highlight is that there is increased long term mortality associated with sepsis that cannot be explained by pre-existing factors such as medical co-morbidities, age, and functional status. The existence of an independent pathobiological septic process has been proposed by numerous studies (8,12) and has been extensively investigated using animal models of sepsis, which would seem to suggest a pro-inflammatory model of accelerated atherosclerosis and chronic immunosuppression. This suggests that earlier aggressive management of sepsis together with longer term emphasis on rehabilitation following sepsis could lead to a significant reduction in long term mortality.…”
mentioning
confidence: 99%
“…In a recently published paper Prescott et al (8) explained an observational matched cohort study which looked to determine if late mortality following sepsis is predominantly explained by pre-existing comorbid pathology or if sepsis itself is responsible for the increased mortality via a pathobiolgical process. In this study late mortality was taken to be 31 days to 2 years, patients with sepsis were matched to three control groups; adults not currently in hospital, patients in hospital with an acute sterile inflammatory process, and lastly patients with non-sepsis infection, patients in each group were matched on the basis of baseline characteristics.…”
mentioning
confidence: 99%